Effects of ChREBP deficiency on adrenal lipogenesis and steroidogenesis. Issue 3 (March 2021) - Takao, Ken; Iizuka, Katsumi; Liu, Yanyan; Sakurai, Teruaki; Kubota, Sodai; Kubota-Okamoto, Saki; Imaizumi, Toshinori; Takahashi, Yoshihiro; Rakhat, Yermek; Komori, Satoko; Hirose, Tokuyuki; Nonomura, Kenta; et al.
Abstract : Carbohydrate response element-binding protein (ChREBP) is critical in the regulation of fatty acid and triglyceride synthesis in the liver. Interestingly, Chrebp −/− mice show reduced levels of plasma cholesterol, which is critical for steroid hormone synthesis in adrenal glands. Furthermore, Chrebp mRNA expression was previously reported in human adrenal glands. Thus, it remains to be investigated whether ChREBP plays a role directly or indirectly in steroid hormone synthesis and release in adrenal glands. In the present study, we find that Chrebp mRNA is expressed in mouse adrenal glands and that ChREBP binds to carbohydrate response elements. Histological analysis of Chrebp −/− mice shows no adrenal hyperplasia and less oil red O staining compared with that in WT mice. In adrenal glands of Chrebp −/− mice, expression of Fasn and Scd1, two enzymes critical for fatty acid synthesis, was substantially lower and triglyceride content was reduced. Expression of Srebf2, a key transcription factor controlling synthesis and uptake of cholesterol and the target genes, was upregulated, while cholesterol content was not significantly altered in the adrenal glands of Chrebp −/− mice. Adrenal corticosterone content and plasma adrenocorticotropic hormone and corticosterone levels were not significantly altered in Chrebp −/− mice. Consistently, expression of genes related to steroid hormone synthesis was not altered. Corticosterone secretion in response to two different stimuli, namely 24-h starvation and cosyntropin administration, was also not altered in Chrebp −/− mice. Taking these results together, corticosterone synthesis and release were not affected in Chrebp −/− mice despite reduced plasma cholesterol levels.